The Application of the Bandongan and Sorogan Methods in Reading Books Learning for Madrasah Aliyah Students - Dzulkarnain, Iskandar; Walad, Akmal; Marzuq, Ahmad (Universitas Yudharta Pasuruan, 2024)
This research discusses the application of the Bandongan and Sorogan methods in Qiroatil Kutub (reading the book) learning as a media for improving the writing skills (maharah al-kitabah) of second-year Aliyah students at Pondok Pesantren Modern Darul Hikmah. Using a descriptive qualitative approach, data were obtained through observation, interviews, and documentation. The research results show that the Qiroatil Kutub learning, which includes the approach, effectively improves the writing skills of the students. Regular practice of reading the gundul texts strengthens vocabulary mastery, understanding of Nahwu and Shorof rules, and the ability to construct sentences in Arabic. In addition, the integrated imla' and insya' activities in the learning process also support the development of writing skills and creative thinking among the students. The main obstacle is the challenges in teaching using the bandongan and sorogan methods, as well as how to implement these methods in the 2nd-year Aliyah class at Pondok Pesantren Modern Darul Hikmah. Through the Bandongan and Sorogan methods, the application of Qiroatil Kutub has proven to be relevant and beneficial for comprehensively developing Arabic language skills.